Textural and Field Relationships of Basement Granitic Rocks, Qaersuarssuk, South Greenland. - Watt, W. Stuart (Meddelelser om Grønland, 1965)
Some textural and field relations of a basement granite in South Greenland are described. The main granite has been formed by granitization but locally there has been later mobilization, mobilized granite intruding non-mobilized granite as dykes. A cross-cutting contact of the granite against a strip of meta-sediment is interpreted as a local late reactivation of the granite that has flushed out the contact to give the sharp, cross-cutting relationship and an intermediate zone formed by contamination. The textures described, principally myrmekite, and albitic rims to plagioclase and myrmekite, are interpreted as due to local changes in ionic concentration resulting in albite growing at the expense of microcline and vice versa. An overall potash-metasomatism has led to the formation of the large potash-feldspar porphyroblasts in a granodioritic matrix.